1999
DOI: 10.1038/sj.jhh.1000817
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of randomised controlled trials (RCT) among healthy normotensive and essential hypertensive elderly patients to determine the effect of high salt (NaCl) diet on blood pressure

Abstract: To examine the effect of chronic NaCl ingestion on blood pressure (BP) in the elderly, a meta-analysis was undertaken of 11 randomised controlled trials of which five included patients у60 years of age only and six included patients with a mean age close to 60 years. The following databases were used: Medline, Embase, Current Contents, The Cochrane Library, the AMI and IPA databases. Mean erect systolic and diastolic blood pressures (SBP/DBP) on chronic (у9 weeks) high and low NaCl diets were recorded, the poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…Consistent with previous studies reporting high salt diet (NaCl) increased risk of hypertension (Tabrizi et al, 2016) and aggravated extant high blood pressure (Alam & Johnson, 1999;Chidambaram et al, 2014). Instant noodle consumers are known to be at risk of high intake of energy, fat, and sodium (J.…”
Section: Discussionsupporting
confidence: 79%
“…Consistent with previous studies reporting high salt diet (NaCl) increased risk of hypertension (Tabrizi et al, 2016) and aggravated extant high blood pressure (Alam & Johnson, 1999;Chidambaram et al, 2014). Instant noodle consumers are known to be at risk of high intake of energy, fat, and sodium (J.…”
Section: Discussionsupporting
confidence: 79%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] An additional MEDLINE search for publications of sodium and potassium trials between January 1995 and March 2001 was performed. Eligibility criteria were (1) randomised design, (2) adult study population (mean age of 18 years or above), and (3) publication date after 1966.…”
Section: Selection Of Randomised Trialsmentioning
confidence: 99%
“…2,3 Meta-analyses of randomised trials found blood pressure falls of 3-5 mmHg systolic and 1-2 mmHg diastolic for sodium reduction in hypertensives, and reductions half this size in normotensives. [4][5][6][7][8][9][10][11][12] For potassium supplementation, blood pressure reductions of more than 3 mmHg systolic and 2 mmHg diastolic have been reported. [13][14][15][16] Blood pressure response to sodium (and possibly also potassium) could be related to initial blood pressure level, age, gender, race, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium. Several meta-analyses and reviews have examined the relationship between sodium intake and blood pressure (603)(604)(605). A review of 32 trials covering 2,635 subjects concluded that moderate reduction of dietary sodium lowers systolic and diastolic blood pressure (603).…”
Section: Hypertensionmentioning
confidence: 99%